Feedback Design Heuristics for Energy Conservation. (April 2014) - Trinh, Kevin; Jamieson, Greg A.
This article reviews a selection of the literature on strategies for and challenges to eliciting energy conservation behaviors from residential and commercial building inhabitants. We highlight visceral influences as one challenge in particular that has been neglected. We argue that feedback design opportunities are underexploited by designers of energy-consuming devices. To help address this problem, we identify and demonstrate feedback design heuristics that human factors/ergonomics practitioners can employ.